Mechanical Behavior of Marine Dual-Carcass Floating Hose Under Torsional Load - Gao Songlin; An Chen; Wei Daifeng; Yang Haoyue; Li Youan (Shiyou jixie)
Torsional load is one of the main loads on offshore floating hose during service， and torsional rigidity is a key mechanical performance parameter of floating hose. The existing floating hoses are designed and manufactured subject to the standards OCIMF 2009 and API 17 K， and there is no detailed description of the torsional mechanical performance indicators and key structural parameters of the floating hose. In this paper， a nonlinear mechanical model of dual-carcass flotation hose under torsional load was built based on Rebar element and Embedded embedding technology. Then， a full-scale torsional test was conducted to verify the accuracy of the finite element model. Thirdly， the clockwise/counterclockwise torsional mechanical performance of the dual-carcass floating hose under fixed/unfixed axial freedom was analyzed. Finally， the sensitivity analysis of the friction coefficient between the inner and outer carcasses of the hose， the inner diameter of the hose， the number of layers of the inner carcass cord， the winding angle of the cord and the pitch of the spiral reinforcement was carried out. The study results show that when the torsional direction of the hose is opposite to the winding direction of the spiral reinforcement， the torsional rigidity is greater， and the radial displacement of the hose is less affected by the deformation direction of the spiral reinforcement. When the end of the hose is not fixed， the axial displacement shows an inward shrinkage trend with the increase of the torsion angle. Affected by the geometric nonlinear factor， the torsional rigidity of the hose increases with the increase of the torsion angle. The inner diameter of the hose， the number of layers of the inner carcass cord， the winding angle of the cord and the pitch of the spiral reinforcement have great influences on the torsional mechanical performance of the hose. The study results provide a reference for the structural design and application of hoses.